Pre-resonant Raman effect of CrO2- 4 in a metasilicate glass - Ziemath, E. C. [UNESP]; Aegerter, M. A.; Melo, F. E A; Moreira, J. E.; Mendes Filho, J.; Dantas, M. S S; Pimenta, M. A. (Elsevier, 1996)
Pre-resonant Raman effect of chromate ion, CrO2- 4, was observed in a metasilicate glass with molar composition 2Na2O · 1CaO · 3SiO2 containing 1.0 wt% of Cr2O3. Raman spectra were measured by the conventional 90° scattering geometry and by the microprobe Raman spectroscopic techniques. The presence of chromate ions in the glass is favoured by the glass composition and oxidizing conditions during the glass melting, and they are responsible for optical absorption bands at 370 and 250 nm. Raman spectrum of the undoped glass presents bands at 625, 860 and 980 cm-1, and the presence of chromate ions gives rise to additional bands at 365, 850 and a shoulder at 890 cm-1. An enhancement of the 850 cm-1 Raman band is observed with decreasing laser exciting wavelength. The exciting frequency dependence of the intensity of this band is discussed in terms of theoretical models given in the literature.